Available transfer capability and least square method - Hojabri, Mojgan; Soheilirad, Mohammadsoroush; Hedayati, Mahdi (Academic Journals, 2012)
In deregulated power industries, accurate and fast calculation of Available Transfer Capability (ATC) for seller in the electricity market is required. In this paper, deterministic ATC will be calculated using algebraic equation and linear optimization by Least Square (LSQR). Probabilistic ATC is also calculated by considering time varying load and load margin. The proposed method will be tested on IEEE 30 bus system. Deterministic ATC results will be compared with Benders, OPF and HCACO and probabilistic ATC results also will be compared with GA and HCACO.